Analisis Asuhan Keperawatan pada Pasien Post Operasi Fraktur Femur dengan Masalah Keperawatan Nyeri Akut dengan Intervensi Inovasi Terapi Benson - Astari, Kadek Ayu; Heri, Mochamad; Putra, G. Nur Widya; Sugiartini, Desak Ketut (Journal of Telenursing (JOTING), 2023)
This study aims to relieve or reduce pain to a level of comfort felt by postoperative femur fracture patients. The method used is descriptive analysis research design with case studies and the number of samples is 1 patient, the instrument is a format Medical surgical nursing care in accordance with the regulations in force at the institution. The results showed that the results obtained from the analysis of one of the patients who received Benson relaxation therapy, namely the patient said that after the Benson relaxation therapy was done, the patient said he felt more calm, less pain. This shows that gasoline relaxation is effective after surgery. Conclusion, based on research giving benson relaxation is very effective for reducing pain in postoperative femoral fracture patients. Keywords: Acute, Benson, Femur Fracture, Pain, Relaxation.